2019
DOI: 10.1039/c9mh00174c
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of biomimetic vasculature for tissue regeneration

Abstract: A simple strategy tailors perfusable and permeable hierarchical microchannel networks from diverse materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 51 publications
0
76
0
Order By: Relevance
“…Incorporating a salt as a sacrificial carrier material into the precursor inks represent another efficient approach to enhance the 3D printability of thermoset polymers. [ 70 ] The 3D‐printed shape before and during curing could be well retained as the sacrificial carrier materials can serve as aggregates to provide mechanical support.…”
Section: Materials Designs For 3d Printabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporating a salt as a sacrificial carrier material into the precursor inks represent another efficient approach to enhance the 3D printability of thermoset polymers. [ 70 ] The 3D‐printed shape before and during curing could be well retained as the sacrificial carrier materials can serve as aggregates to provide mechanical support.…”
Section: Materials Designs For 3d Printabilitymentioning
confidence: 99%
“…They also showed that incorporating sodium chloride particles into ink formulations could result in the formation of gradient porous structures after soaking in DI water, which are responsible for the rapid, programmable bending movement of 3D printed objects. [ 70 ]…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Lei et al implanted perfusable engineered tissues on infarcted myocardium subcutaneously and epicardially. Compared to general 3D printed tissues without channels, the perfusable tissues possessed better tissue integration and treated myocardial infarction more efficiently …”
Section: Applications Of Biomimetic Vascularizationmentioning
confidence: 99%
“…Recently, extrusion-based three-dimensional (3D) printing technology has been widely applied for producing biomaterials in regenerative medicine and promoted significant innovations [18][19][20][21][22]. During printing, viscoelastic inks are extruded out of a 3D printer's nozzle as printed fibers, which are deposited into patterns layer by layer when the nozzle moves [23,24].…”
Section: Introductionmentioning
confidence: 99%